Hexafluoroisopropanol mediated benign synthesis of 2H-pyrido[1, 2-a]pyrimidin-2-ones by using a domino protocol. (30th October 2017) - Alsharif, Zakeyah; Ali, Mohamad Akbar; Alkhattabi, Hessa; Jones, Derika; Delancey, Evan; Ravikumar, P. C.; Alam, Mohammad A.
Abstract : A domino strategy has been used for the synthesis of 2 H -pyrido[1, 2- a ]pyrimidin-2-ones. Abstract : A domino strategy has been used for the synthesis of 2 H -pyrido[1, 2- a ]pyrimidin-2-ones. Four sequential reactions: aza-Michael addition, water elimination, intramolecular acyl substitution, and [1, 3]- H shift were observed in this domino protocol. Hexafluoroisopropanol is used as a promotor and recyclable solvent in this cascade process. The availability of inexpensive 2-aminopyridines and a wide variety of Michael acceptors such as commercially available acrylates and unactivated Baylis–Hillman adducts makes this methodology a huge reservoir of novel fused N-heterocycles as bioactive and potential therapeutic agents. The reaction mechanism has been proposed and rationalized by density functional theory calculations. Products are obtained in up to 95% yield.